The Effect of Ergonomic Exercise on Blood Pressure Reduction in Hypertensive Patients at the South Tinggede Health Center in the Tinggede Community Health Center Working Area - Abadi, Siti Rafika; Ahmil, Ahmil; Lestari, Katrina Feby; Rahman, Abdul (Department of Publication of Inspirasi Elburhani Foundation Desa. Pamokolan, Kecamatan Cihaurbeuti, Kabupaten Ciamis, Provinsi Jawa Barat, Indonesia, 2025)
Background & Objective : Hypertension is one of the most common non-communicable diseases in society and is known as the “silent killer” because its symptoms often go unnoticed. Data shows that the prevalence of hypertension in Central Sulawesi is quite high. Non-pharmacological management such as ergonomic exercises is a potential alternative in lowering the blood pressure of patients with hypertension. This study aims to analyze the effect of ergonomic exercises on lowering blood pressure in hypertensive patients at the Tinggede Selatan Health Center in the Tinggede Public Health Center working area. Method: This study used a quantitative approach with a pre-experimental one-group pretest-posttest design. The sample consisted of 35 people with hypertension, selected using total sampling technique. The intervention, which was ergonomic exercises, was given twice a week for two weeks. Result: Before the intervention, 21 respondents (60.0%) were in stage 1 hypertension, and after the intervention, there was a significant decrease in blood pressure in the prehypertension category in 21 respondents (60.0%). Statistical testing using the Wilcoxon test yielded a p-value of 0.000 (< 0.05). Conclusion: Ergonomic exercises have been proven to have a significant effect in lowering blood pressure in people with hypertension.